2009
DOI: 10.1269/jrr.08123
|View full text |Cite
|
Sign up to set email alerts
|

Differential Free Radical Scavenging Activity and Radioprotection of Caesalpinia Digyna Extracts and its Active Constituent

Abstract: Two extracts E1and E2 were prepared from the dried root of the plant Caesalpinia digyna by extracting with solvents of different polarity. The extracts were standardized with respect to a polyphenol, bergenin, by LC- MS analysis and they were subjected to free radical scavenging activity and in vitro radioprotection studies. Free radical reactions were carried out with superoxide, hydroxyl, and peroxyl radicals and DPPH. In vitro radioprotecting activity was studied by following their effect on gamma-radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This hypothesis is supported by the results of the LC‐MS/MS analysis, which revealed the presence of betanin and its derivatives, flavonol glycosides as well as hydroxycinnamic acid derivatives in the tested pitaya extracts. Moreover, our findings also indicate that the polyphenols present in the tested pitaya extracts play important antioxidant roles, supported by the results of several recent studies (Tachakittirungrod and others 2007; Soo‐Jin and others 2008; Singh and others 2009).…”
Section: Resultssupporting
confidence: 90%
“…This hypothesis is supported by the results of the LC‐MS/MS analysis, which revealed the presence of betanin and its derivatives, flavonol glycosides as well as hydroxycinnamic acid derivatives in the tested pitaya extracts. Moreover, our findings also indicate that the polyphenols present in the tested pitaya extracts play important antioxidant roles, supported by the results of several recent studies (Tachakittirungrod and others 2007; Soo‐Jin and others 2008; Singh and others 2009).…”
Section: Resultssupporting
confidence: 90%
“…Bergenin (1) itself is a good scavenger of hydroxyl radicals but not so effective in scavenging other free radicals like superoxide radical and DPPH [33,35,41,42,50,52,55,64,110,111,148,188,189]. Significant antioxidant activity of bergenin in hydrogen peroxide, ABTS, DPPH and inhibition of lipid peroxidation assays with IC 50 values 32.54, 75.06, 165.35 and 365.12 μg/mL, respectively, was reported by Srinivasan et al [54].…”
Section: Antioxidant Activitymentioning
confidence: 95%
“…It exhibited melanogenesis inhibitory activity in α-melanocyte-stimulating hormone (α-MSH)-stimulated B 16 melanoma cells and therefore may be valuable as the potential skin whitening agents. Bergenin exhibited protection effect in γ-radiation induced DNA (pBR322) damage [55]. No antitumor activity of bergenin on human gastric carcinoma cell line MGC-803 was reported [52].…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…(Family: Fabaceae; Subfamily: Caesalpinioideae), a large, scandent, prickly shrub growing wild in the shrub forests of the eastern Himalayas, Nilgiris, Ceylon, Malaya islands etc. have been studied for its free radical scavenging property, and protection from oxidative damages (Srinivasan et al, 2007;Singh et al, 2009). Singh et al (2009) showed that the methanolic root extract (E1; for polar constituents) and acetone root extract (E2; for non-polar constituents), standardized with bergenin (the active constituent of the plant) content is a potent inhibitor of superoxide (O 2…”
Section: Caesalpinia Digynamentioning
confidence: 99%